Modelagem e simulação da secagem de frutos de café em um secador de bandejas vibradas - Rezende, Diogo Rodrigues de (2011)
The School of Chemical Engineering, Federal University of Uberlândia has been conducting studies of expression in the drying of coffee fruits using vibrated tray dryer with recycle. Among the work carried it is emphasized of Sfredo (2006), who did the study of dispersion in the coffee fruit dryer described initially. Data from the drying of coffee fruits obtained by this author, who conducted a detailed description of their experimental designs were used as the basis for application of mathematical models that can properly simulate the drying of coffee fruits in vibrated tray dryer with recycle. The use of mathematical models for drying of coffee fruits provide the simulation of the drying process considering the influence of relevant variables in the process. For modeling and simulation of mathematical models was made a literature review of thermo-physical properties of coffee fruits, which are required for accurate representation of the drying kinetics, and important in the simulation and design of dryers. A study of dimensional analysis was elaborated in which they were identified in the relevant dimensionless numbers used in drying and process simulation. There was selected three mathematical models (Arrieche, 2007, Hussain and Dincer, 2003; Chemkhi et al. 2005) in order to compare the results of simulations among themselves and with those obtained by Sfredo (2006). The models evaluated are able to calculate humidity and temperature of several internal coordinates to the fruits of coffee. In these simulations were changes of variables and applying the method of orthogonal collocation for the solution of partial differential equations used in the models. The results show that the three models adequately represented the drying of coffee fruits in trays vibrated.